Forgiveness level Among Talented Athletes - Hammuri, Khaled (Journal of Physical Education, 2022)
The study aimed to recognize the forgiveness level among   athletically gifted the study sample consisted of (105) students, at the Directorate of Education in of Al koura District, who were intentional chosen? The analytical descriptive method was adopted, as also the forgiveness scale prepared by Rye et al (2001), was applied on the study sample, the study results indicated the following: The forgiveness level among the athletically gifted students was high. there were statistically significant differences (α≥0.05) not appropriate word to the effect of gender in the total degree of forgiveness scale and the differences were in favor of males. there were statistically significant differences (α≥0.05) not appropriate word to the effect of game type in the total degree of forgiveness scale and the differences were in favor of team games.